Analysis of Illegal Fishing Issues in Meranti Islands Regency and Its Impact on Marine Ecosystem Sustainability - Firmansyah, Ridho (IHSA Institute, 2024)
Indonesia, as the largest maritime nation with over 17,000 islands and vast oceanic areas covering two-thirds of its territory, possesses significant potential in the marine sector. However, practices of illegal fishing, often conducted by foreign and local fishermen in waters such as those of the Meranti Islands Regency in Sumatra, threaten the sustainability of marine ecosystems and the livelihoods of local fishermen. This research aims to examine the enforcement efforts against illegal fishing in the region, including both preventive and repressive measures implemented by the Marine and Fisheries Office and the Water Police. The research method used is observational, with data collection techniques involving direct interviews with officials from the Water Police and the Marine and Fisheries Office as respondents. The findings indicate that preventive measures include legal education and routine patrols, while repressive measures encompass the arrest and examination of lawbreakers. However, law enforcement faces various challenges, such as limited resources and facilities, low public awareness of the impacts of illegal fishing, and economic factors that drive some fishermen to engage in illegal practices. Therefore, enhancing oversight, ongoing legal education, and providing necessary resources are essential to preserving marine resources and ensuring effective law enforcement in the Meranti Islands Regency